Conversational Implicature in Quranic Narratives: The Last Verses in Surat Al-Maida as a Model - SAMIR, Hossam El-Din; Al-Sagheer, Ahmed Mohamed; ALGHAZALI, Fawzi (Journal of Posthumanism, 2025)
Undoubtedly, the Holy Quran represents a perfectly structured text that is miraculous on all linguistic levels; phonetically, grammatically, syntactically, semantically, and pragmatically. Therefore, it has long been worthy of scholars’ and analysts’ attention and scrutiny. The Holy Quran is an eternal text that is not limited to a particular era of time. It is unique in its nature. Pragmatically, it is a conversational text between the Almighty creator-since it is His words- and the recipient, Prophet Mohamed, peace be upon him (PBH) who was the assigned prophet to deliver the message of Allah (God Almighty) as represented in the linguistic miracle of the Holy Quran. Such a unique miracle was a daring challenge for all eloquent and talented Arabs at the time. As proven in several linguistic studies, meaning is not confined to the surface or literal phrasing or directives, prohibitions, or interrogatives, but it might transcend beyond that to refer to indirect and deep meanings. Such implicit meanings depend primarily on their context. In the present study, researchers investigate conversational implicatures in the stories of the Glorious Quran. Particularly, the researchers examine the last verses of the Quranic Surat Al-Ma’idah as a model for application and analysis.